Micropapillary bladder cancer: A review of the University of Texas M. D. Anderson Cancer Center experience with 100 consecutive patients - Kamat, Ashish M.; Dinney, Colin P. N.; Gee, Jason R.; Grossman, H. Barton; Siefker‐Radtke, Arlene O.; Tamboli, Pheroze; Detry, Michelle A.; Robinson, Tracy L.; Pisters, Louis L. (Cancer, 2007)
Micropapillary bladder carcinoma is a rare variant of urothelial carcinoma. To improve understanding of this disease, the authors performed a retrospective review of their experience. The authors reviewed the records of 100 consecutive patients with micropapillary bladder cancer who were evaluated at The University of Texas M. D. Anderson Cancer Center. The mean age of the patients was 64.7 years, with a male:female ratio of 10:1. The TNM stage of disease at the time of presentation was Ta in 5 patients, carcinoma in situ (CIS) in 4 patients, T1 in 35 patients, T2 in 26 patients, T3 in 7 patients, T4 in 6 patients; N+ in 9 patients, and M+ in 8 patients. Kaplan-Meier estimates of 5-year and 10-year overall survival (OS) rates were 51% and 24%, respectively. Bladder-sparing therapy with intravesical bacillus Calmette-Guerin therapy was attempted in 27 of 44 patients with nonmuscle-invasive disease; 67% (18 patients) developed disease progression (>or=cT2), including 22% who developed metastatic disease. Of 55 patients undergoing radical cystectomy for surgically resectable disease (<or=cT4a), 23 received neoadjuvant chemotherapy and 32 were treated with initial cystectomy, with no significant difference noted in stage distribution between the 2 groups. For the 23 patients treated with neoadjuvant chemotherapy, the median OS was 43.2 months with 32% of patients still alive at 5 years. For the 32 patients treated with initial cystectomy, the median survival had not been reached at the time of last follow-up, with 71% still alive at 5 years. Micropapillary bladder cancer is associated with a poor prognosis. Intravesical therapy appears to be ineffective in this disease and patients with surgically resectable disease should be offered early radical cystectomy.